Causality of genetically predicted solid cancers on risk of sepsis: insights from Mendelian randomization - Linjie Qiu; Shiyu Chen; Jia Zhong; Yan Zhang; Kai Zhang (Discover Oncology)
Abstract Objective Some studies have found that solid cancer and sepsis are linked. The primary objective of this study is to explore this connection further, investigating the causal effect of solid cancer on sepsis by applying Mendelian randomization (MR). Methods Using genome-wide association study (GWAS) data from the Medical Research Council-Integrative Epidemiology Unit database, we conducted a bidirectional two-sample Mendelian randomization (MR) analysis to test the causal association between solid cancers (10 GWAS, 1,345,730 samples) and sepsis (2 GWAS, 1,288,566 samples) in European ancestry. In the context of multivariable MR analysis, lifestyle risk factors such as body mass index (BMI) were incorporated, with relevant clinical interventions taken into account. Results The two-sample MR analysis suggested a causal relationship between renal cancer and sepsis (OR = 1.051, 95% CI = 1.019–1.085, PIVW = 1.800E-03). Renal cancer (OR = 1.064, 95% CI = 1.011–1.120, PIVW = 1.60E-02), BMI (OR = 1.315, 95% CI = 1.176–1.471, PIVW = 1.25E-06), and smoking (OR = 1.139, 95% CI = 1.009–1.286, PIVW = 3.65E-02) showed a significant association with sepsis in our lifestyle multivariable MR analysis. Reverse MR analysis indicates that sepsis may prevent renal cancer. (OR = 0.924, 95% CI = 0.865 -0.988, PIVW = 2.060E-02). Conclusions Our findings suggest renal cancer is correlated with the occurrence of sepsis. This association is partially influenced by BMI and smoking. Unexpectedly, sepsis may act as a protective effect against renal cancer.